"حوكمة المسؤولية الاجتماعية للمؤسسات - دراسة حالة بعض المؤسسات الاقتصادية في ولاية الوادي - " - الهادي, بكوش; باسي, سعد; العايش, ليدي; نجاة, باسي (University of eloued جامعة الوادي, 2021)
"الملخص: تهدف هذه الدراسة إلى الكشف عن مدى امكانية تطبيق المسؤولية الاجتماعية في المؤسسات، وما علاقة هذه المسؤولية بحوكمة المؤسسات، حيث قمنا بالاعتماد على المنهج الوصفي في الجانب النظري، وأسلوب المسح الاجتماعي بالجانب التطبيقي اعتمادا على تصميم استبيان لجمع المعلومات من مجتمع، فإن ما يمكن ان نستنتجه من خلال الدراسة التطبيقية والتي تمحورت حول إعداد استبيان خاص بحوكمة المسؤولية الاجتماعية ، والذي تم تقسيمه الى قسمين، قسم خاص بالمعلومات الشخصية للمستجوب بغية معرفة خصائص عينة الدراسة ، وقسم خاص بمحاور الدراسة والتي رأينا فيها أن تقسم حسب متغيرين احدهما مستقل والاخر تابع ، فاخترنا ان تكون اليات حوكمة المؤسسات مؤشرا ومتغيرا مستقلا يؤثر على حاكمية المؤسسات ومدى تبني المؤسسات لها فتصبح المسؤولية الاجتماعية او تطبيقها في المؤسسات الاقتصادية متغيرا تابعا ، ولقد وضعنا ثلاث فرضيات من اجل الاجابة على تساؤلات الدراسة التطبيقية وهم فرضية العلاقة من خلال معامل الارتباط واختباره احصائيا والذي وجدنا من خلاله ان الاليات الداخلية فقط لها علاقة بتطبيق المسؤولية الاجتماعية في المؤسسات، اما فرضية الفرق فوجدنا انه لا توجد أي فروقات بين متوسطات اجابات العينة تعزى للمعلومات الشخصية ، واخيرا فرضية التأثير والتي اكدت فرضية العلاقة حيث وجدنا ان الاليات الداخلية للحوكمة فقط تؤثر على تطبيق الحوكمة في المؤسسات. ""Abstract: This study aims to reveal the extent to which social responsibility can be applied in institutions, and what is the relationship of this responsibility to corporate governance, as we have relied on the descriptive approach in the theoretical aspect, and the method of social survey in the practical aspect depending on the design of a questionnaire to collect information from a community, what we can conclude Through the applied study, which centered on preparing a questionnaire for the governance of social responsibility, which was divided into two parts, a special section for the personal information of the interviewee in order to know the characteristics of the study sample, and a special section for the study’s axes, which we saw as divided according to two variables, one independent and the other dependent. The mechanisms of corporate governance are an indicator and an independent variable that affects the governance of institutions and the extent to which institutions adopt them, so that social responsibility or its application in economic institutions becomes a dependent variable. Only the internal mechanisms have anything to do with the application of social responsibility in institutions. As for the difference hypothesis, we found that no There are any differences between the averages of the sample answers due to personal information, and finally the impact hypothesis, which confirmed the relationship hypothesis, where we found that only the internal mechanisms of governance affect the application of governance in institutions. Keywords: social responsibility, corporate governance, dimensions of social responsibility, determinants and mechanisms of corporate governance."
ماستر محاسبة
Keywords: المسؤولية الاجتماعية، حوكمة المؤسسات، أبعاد المسؤولية الاجتماعية، محددات وآليات حوكمة الشركات.; social responsibility, corporate governance, dimensions of social responsibility, determinants and mechanisms of corporate governance.